Publicly Available Geographic Information Sources and Common Analysis Tools: AE550/AE550, 01/2021 - Shin, Satbyeol; Her, Young Gu (EDIS, 2021)
Geographic information and geospatial data are vital in many practical fields, including precision agriculture, natural resources management, flood zone mapping and management, and environmental assessment. This 6-page publication introduces publicly available geospatial data, including elevation, land use, soil, satellite imagery, and other thematic maps and GIS software commonly used in spatial analysis. Written by Satbyeol Shin and Young Gu Her, and published by the UF/IFAS Department of Agricultural and Biological Engineering, January 2021.